Yield and mineral nutrition of soybean, maize, and congo signal grass as affected by limestone and slag - Castro, Gustavo Spadotti Amaral; Crusciol, Carlos Alexandre Costa [UNESP] (FapUNIFESP (SciELO), 2013)
The objective of this work was to evaluate the efficiency of superficial applicationof limestone and slag, and their effects on soil chemical attributes and on yield and mineral nutrition of soybean, maize, and Congo signal grass (Urochloa ruziziensis). The experiment was carried out in a Rhodic Hapludox under no tillage system. The treatments consisted of the use of limestone or slag (silicates of calcium and magnesium) to correct soilacidity, and of a control treatment without the use of soil correctives. Rates were calculated in order to raise soil base saturation up to 70%. Soybean was sown in November 2006and maize in December 2007. Congo signal grass was sown right after the harvests of soybean and maize, and it was cropped during the offseasons. Soil chemical attributes were evaluated at 6, 12, and 18 months after the application of the corrective materials. Slag isan efficient source for soil acidity correction, being able to raise the exchangeable base levels in the soil profile faster than lime. Both limestone and slag increase dry matter yield of Congo signal grass, and grain yield of soybean and maize. Slag is more effective in improving maize grain yield.

O objetivo deste trabalho foi avaliar a eficiência da aplicação superficial de calcário e escória de siderurgia e seus efeitos nos atributos químicos do solo e na produtividade e nutrição de soja, milho e capim-ruziziensis (Urochloa ruziziensis). O experimento foi conduzido em Latossolo Vermelho distroférrico, sob sistema de semeadura direta. Os tratamentos consistiram do uso de calcário e de escória de siderurgia (silicatos de cálcio e magnésio), para corrigir a acidez do solo, e de uma testemunha sem aplicação de corretivos. As dosagens foram calculadas com o intuito de elevar a saturação por bases a 70%. A soja foi semeada em novembro de 2006 e o milho em dezembro de 2007. O capim-ruziziensis foi semeado logo após as colheitas da soja e do milho e foi cultivado durante as entressafras. Os atributos químicos do solo foram avaliados aos 6, 12 e 18 meses após a aplicação dos corretivos. A escória é uma fonte eficiente para correção da acidez do solo e é capaz de aumentar o nível de bases trocáveis no perfil do solo mais rapidamente do que o calcário. Tanto o calcário como a escória aumentam a produção de matéria seca do capim-ruziziensis e a produção de grãos de soja e milho. A escória é mais eficiente em elevar a produtividade do milho.
Produtividade e nutrição mineral de soja, milho e capim-ruziziensis influenciados por calcário e escória de siderurgia
Keywords: No tillage; Silicon; Soil chemical attributes; Subsuperficial acidity; Superficial liming; Yield components.